Analisis Risiko Produksi Usahatani Padi Organik - Prayoga, Ryan; Lubis, Mitra Musika (Hasanuddin University, 2024)
This research aims to determine the sources of production risk in organic rice farming in Lubuk Bayas Village, Perbaungan District, Serdang Bedagai Regency. What is the level of production risk in organic rice farming in Lubuk Bayas Village, Perbaungan District, Serdang Bedagai Regency and what efforts are being made to minimize it? production risks. The population of organic rice farmers in Lubuk Bayas Village is 25 people. The sample was determined using the census method so that the sample used was 25 people, data collection was carried out by observation, interviews and filling out questionnaires. Meanwhile, data analysis uses standard deviation and coefficient of variation analysis. The research results show that the sources of risk for organic rice farming production in Lubuk Bayas Village include land processing, planting, fertilizing, post-harvest, pests and diseases, climate, and weather. level of production risk from the coefficient of variation (CV) is 0.57 in planting season A and 0.58 in planting season B. Where both seasons are < 1, organic rice farming in Lubuk Bayas Village, Perbaungan District, Serdang Bedagai, districts has a low or small production risk. Then efforts to minimize the risks of organic rice farming production include cleaning irrigation canals, raising beds, carrying out replanting, making reservoirs, harvesting on time, using machines when harvesting, and carrying out routine checks as well as carrying out care and maintenance by applying organic fertilizer, vegetable pesticides, and liquid organic fertilizer.